Day 2 Wed, March 25, 2020 2020
DOI: 10.2118/199802-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Success Story: Utilizing Different Variables in Design and Execution of Coiled Tubing Extended Reach Milling Operations

Abstract: The Shell Canada Fox Creek asset is located in West Central Alberta and has development activities focused on the Duvernay reservoir. Efficient, horizontal, plug and perf wells, are key to delivering economic production from this unconventional light tight oil play. Unlocking more acreage per well, through the application of longer laterals, contribute significantly to CAPEX reduction. Although intervention-less completions are a future aspiration, well intervention is still required for plug removal to assure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Nevertheless, it is essential to note that this may be applicable when there are logistics issues. [14] Showed that the use of generation four CT and the use of fluid rheology improved cleaning efficiency. The study demonstrated that optimizing well trajectory, string design, incorporating real-time monitoring.…”
Section: Authors Study Findingsmentioning
confidence: 99%
“…Nevertheless, it is essential to note that this may be applicable when there are logistics issues. [14] Showed that the use of generation four CT and the use of fluid rheology improved cleaning efficiency. The study demonstrated that optimizing well trajectory, string design, incorporating real-time monitoring.…”
Section: Authors Study Findingsmentioning
confidence: 99%